8800 years of high-altitude vegetation and climate history at the Rutor Glacier forefield, Italian Alps. Evidence of middle Holocene timberline rise and glacier contraction. (1st April 2018) - Badino, Federica; Ravazzi, Cesare; Vallè, Francesca; Pini, Roberta; Aceti, Amelia; Brunetti, Michele; Champvillair, Elena; Maggi, Valter; Maspero, Francesco; Perego, Renata; Orombelli, Giuseppe
Abstract: Sedimentary archives at or near the timberline ecotone in Alpine glaciated areas contain records to study Holocene climate change and the interplay between climate, ecosystems, and humans. We focused on records of timberline and glacier oscillations in the Rutor Glacier forefield (Western Italian Alps) in the last 8800 years. Human activity in this area was negligible for most of the Holocene. We adopted an integrative stratigraphic approach including proxies for glacier advance and timberline estimation, sedimentary events, and reconstructed temperatures. Changes in timberline ecotone correlate to climate until the Middle Ages. Pollen-stratigraphic evidence of a primary plant succession highlights a lag beween local deglaciation and the first reliable 14 C age. The radiocarbon chronology points to a prolonged phase of glacier contraction between 8.8 and 3.7 ka cal BP. Even later the glacier remained within its LIA limits. Between 8.4 and 4 ka cal BP MAT-inferred TJuly fluctuated near 12.4 °C, ca. 3.1 °C higher than today. During this period, a Pinus cembra forest belt grew at 2600 m asl with an upper limit of tree groves placed 434 ± 310 m above the current open forest limit. This Holocene phase of thermal maximum ended between 3.98 and 3.51 ± 70 ka cal BP and with a substantial rearrangement of forest composition; temperature reconstruction shows a decrease of 1.8 °C. This climate deterioration concluded the Subboreal thermal optimum, mirroring glacial advances widely documented in the Alps. The Rutor Glacier advanced at ca. AD 1093 ± 65, and remained inside the LIA maximum extent. The LIA started since AD 1594, and culminated between AD 1751 and 1864. Highlights: Between 8.8 and 3.7 ka cal BP a long phase of contraction of the Rutor Glacier occurred. Early plant pioneering of the glacier forefield is palynologically recorded. Reconstructed TJuly shows a lowering of 1.7 °C related to the 8.2 ka event. Between 8.4 and 4 ka cal BP a Pinus cembra forest belt established at 2600 m asl At AD 1093 ± 65 the Rutor Glacier reached a size close to its LIA maximum extent.